Should adults with diabetes mellitus be vaccinated against hepatitis B virus? A systematic review of diabetes mellitus and the progression of hepatitis B disease - Zobair Younossi; Katrin Kochems; Marc de Ridder; Desmond Curran; Eveline M. Bunge; Laurence de Moerlooze (Taylor & Francis Group, 2017)
Despite the burden of diabetes mellitus (DM), little is known about the role of this and other metabolic syndromes on the severity of hepatitis B virus (HBV) chronicity and liver disease progression. The value of hepatitis B vaccination and its impact on liver diseases and HCC has been largely demonstrated, adult vaccination coverage is however suboptimal and DM diagnosis represents an opportunity for the HCP to discuss hepatitis B and other adult vaccinations. We performed a systematic literature search to identify studies (January 2000 to January 2017) describing liver disease progression among patients with HBV by DM status. Risk factors were assessed including the relationship between HBV and non-alcoholic steatohepatitis (NASH). Data were extracted systematically and assessed descriptively. Twenty articles described liver disease progression and one article evaluated NASH among subjects with HBV by DM status. Fourteen articles reported that DM as a predictor for the outcome, including delayed seroclearance, cirrhosis, hepatocellular carcinoma, transplant/mortality and death, whereas no association on liver outcomes was found in 7 studies. In summary, our review suggests that DM is associated with the progression of severe liver outcomes in adults with HBV, although more studies are needed to understand the benefits of HBV vaccination in adults with DM and liver-diseases.